Peningkatan Kesadaran Nilai Bhinneka Tunggal Ika untuk Mencegah Rasisme yang Terjadi di Indonesia - Felycia Jannice Michelle; Jovanka Nelly Sagyta; Salma Koulan (Universitas Palan, 2024)
“Bhinneka Tunggal Ika” is the official motto of Indonesia, meaning “Different but still one.” It emphasizes unity in diversity, highlighting the importance of unity amidst Indonesia’s ethnic, religious, racial and cultural diversity. Efforts such as multicultural education, social campaigns, and public policies will be highlighted as strategic measures to address the problem of racism in Indonesia. The method used in this research is a quantitative approach with data collection techniques through distributing Google Form links through each member’s social media account. This research aims to increase the awareness of the Indonesian people of the values of Bhinneka Tunggal Ika as the foundation of the unity of diversity in Indonesia, so that behaviors that can affect the emergence of racism can be avoided. The results of this study found that some people are aware of racist behavior that still occurs around them, while others are not. It is hoped that this research can be a useful guide for efforts to prevent and overcome racism in Indonesia, as well as strengthen a shared commitment to creating an inclusive, tolerant and respectful society.